Analysis of Metabolit and Antibacterial Control of Mengkudu Leaf Extract (Morinda citrifolia) on the Bacteria of Aeromonas hydrophila - Yora Utami Putri Pertiwi; Arief Prajitno; Mohamad Fadjar (Research Journal of Life Science, 2019)
A. hydrophila is an anaerobic facultative bacterium, which is a bacterium that can develop in conditions with or without oxygen. Therefore, it is necessary to use alternative materials that can be used to eliminate A. hydrophila, one of which is to use herbal medicines. The purpose of this study was to determine the content of active compounds in mengkudu leaf extract (M. citrifolia) using the disc test method. To test the content of secondary metabolites, phytochemical testing and FTIR (Fourier Transform Infrared Spectroscopy) were carried out. The results obtained are 100 ppm which is the minimum concentration that can inhibit the growth of A. hydrophila. Phytochemical test results obtained crude extract of positive mengkudu leaves alkaloids, saponins, triterpemoid and flavonoids. And in the FTIR test the most dominant content of phenol compounds contained in Mengkudu leaf extract which has a very important function that can be used as an antibacterial in this study. Further research is expected to carry out more in-depth characterization testing of active compounds through several tests including using LCMS or GCMS to determine the active ingredient of mengkudu leaves.